ANALISIS KETAHANAN PANGAN RUMAH TANGGA PETANI PADA MASA PANDEMI COVID-19 MELALUI BERUSAHATANI DARI RUMAH (FARM FROM HOME) - Kustiawati Ningsih; Sustiyana Sustiyana (Sepa, 2022)
To meet the family's food needs during the Covid-19 pandemic, the farmer households of Blumbungan Village do farming from home, one way is to use their yard by cultivating vegetables. Vegetable cultivation in the yard has a strategic role to increase the diversity of food consumption patterns and increase the nutrition of farmer households, and is expected to be able to meet the needs of vegetables at the household level while at the same time assessing the high aesthetic value. The purpose of this study was to examine in depth the analysis of the food security of farmer households during the Covid-19 pandemic through farming from home (farm from home). The research method uses descriptive analytical method, by determining the sample by quota, namely the number of 30 farmer households in Blumbungan Village, Larangan District, Pamekasan Regency. Data analysis was carried out descriptively and equation analysis of Food Expenditure Proportion (PPP), Energy Consumption Level (TKE), and quadrant analysis. The results showed that the household food expenditure of farmers was greater than the non-food expenditure. The degree of food security of farmhouses based on the proportion of expenditure and the level of energy consumption is in the category of food insecurity at 43.33%, food shortages at 50% and food insecurity at 6.67%. So it can be concluded that farming from home through corn farming, use of yard land and livestock has a role in the degree of food security of farmers' households.